Relationship between disorders of the intestinal microbiota and heart failure in infants with congenital heart disease - Zhang, Qi-Liang; Chen, Xiu-Hua; Zhou, Si-Jia; Lei, Yu-Qing; Huang, Jiang-Shan; Chen, Qiang; Cao, Hua (Frontiers in Cellular and Infection Microbiology, 2023)
Purpose: There is a close relationship between the intestinal microbiota and heart failure, but no study has assessed this relationship in infants with congenital heart disease. This study aimed to explore the relationship between heart failure and intestinal microbiota in infants with congenital heart disease. Methods: Twenty-eight infants with congenital heart disease with heart failure admitted to a provincial children's hospital from September 2021 to December 2021 were enrolled in this study. Twenty-two infants without heart disease and matched for age, sex and weight were selected as controls. Faecal samples were collected from every participant and subjected to 16S rDNA gene sequencing. Results: The composition of the intestinal microbiota was significantly disordered in infants with heart failure caused by congenital heart disease compared with infants without heart disease. At the phylum level, the most abundant bacteria in the heart failure group were Firmicutes, Actinobacteria, Proteobacteria and Bacteroidetes, and the most abundant bacteria in the control group were Firmicutes, Proteobacteria, Actinobacteria and Bacteroidetes. At the genus level, the most abundant bacteria in the heart failure group were Enterococcus, Bifidobacterium, Subdoligranulum, Shigella, and Streptococcus, and the most abundant bacteria in the control group were Bifidobacterium, Blautia, Bacteroides, Streptococcus and Ruminococcus. The alpha and beta diversities of the gut bacterial community in the heart failure group were significantly lower than those in the control group (p<0.05). Compared with the control group, retinol metabolism was significantly downregulated in the heart failure group. Conclusion: Heart failure in infants with congenital heart disease caused intestinal microbiota disorder, which was characterized by an increase in pathogenic bacteria, a decrease in beneficial bacteria, and decreases in diversity and richness. The significant downregulation of retinol metabolism in the intestinal microbiota of infants with heart failure may be related to the progression of heart failure, and further study of the underlying mechanism is needed.